Effect of loaded organic phase containing mixtures of silicon and aluminum, single iron on extraction of lanthanum in saponification P507-HCl system - 吴文远 张丰云 边雪 薛首峰 尹少华 郑强 (Journal of rare earths, 2013)
Emulsification troubled normal extraction process of rare earths due to the existence of non-rare earth impurities, especially Si, Al and Fe. Against this background, the effect of emulsification caused by Si, Al and Fe on the La extraction with saponification P507 （2-ethylhexyl phosphonic acid mono-2-ethylhexyl ester） in chloride medium was systematically investigated. A series of experiments were carried out to study the relationship of the extraction capacity of La and the concentration of impurities. ZPM-203 polarizing microscope was applied to investigate the morphology of emulsification, and the cation exchange extraction mechanism of Fe and Al as well as La was clarified by IR spectra. The results showed that a low concentration of Si in organic phase would aggravate the emulsification with Al, and the formation of ME （micro emulsion） and club-shaped polymer would result in emulsification in the extraction of mixtures of Si and Al, single Fe, respectively. Furthermore, the accumulation of impurity such as Si, Al and Fe in the organic phase would severely reduce the extraction capacity of La simultaneously.